Från lön till skön beskattning? En analys av förslaget om bortplockat löneuttagskrav i SOU 2024:36 Förenkla och förbättra, i ljuset av neutralitetsprincipen - Svensson,Hjalmar (2025)
The close company rules in Chapter 57 of the Swedish Income Tax Act (1999:1229) contain special provisions on how monetary compensation to active owners in close companies is to be divided between return on invest-ed capital and remuneration for performed work. The primary purpose of these rules is to prevent income conversion, and thereby achieving neutral taxation of taxpayers. Dividends and capital gains up to a certain amount, the threshold amount, are taxed as capital income, whereas any excess is taxed as income from employment. The threshold amount can be increased if the shareholder includes a wage-based amount calculated on the compa-ny’s total payroll expenses. However, in order to be entitled to this, the shareholder must meet a minimum salary requirement, known as the salary withdrawal requirement. In the governement report SOU 2024:36 Förenkla och förbättra! (Simplify and improve!), a number of proposed amendments to the close company rules are presented. Among other things, the inquiry proposes that the salary withdrawal requirement is abolished and replaced by a standardized wage deduction. This thesis addresses the background and design of the salary withdrawal requirement under the current regulatory framework, as well as what the proposed abolition of this requirement would mean for the close company rules. Thereafter a subsequent chapter is dedicated to the neutrality principle and its significance within Swedish tax law. Finally, both the current and the proposed regulatory frameworks are analyzed in light of their consisten-cy with the neutrality principle. In summary, the thesis concludes that the inquiry’s proposal to replace the salary withdrawal requirement with a standardized wage deduction better fulfills the requirement for neutral taxation. The salary withdrawal require-ment currently disqualifies certain shareholders who are in fact intended to benefit from the wage-based amount, simply because their market salary is too low. As a result, the determining factor becomes the industry in which the shareholder operates, which constitutes an obvious lack of neutrality in comparison with other business structures. Furthermore, shareholders who currently calculate wage-based amount solely based on their own salary will no longer be able to do so, as a standardized deduction would be applied. Since these taxpayers are not intended to fall within the scope of the wage-based rules, this change also contributes to more neutral taxation in relation to other wage earners.
Keywords: skatterätt; fåmansföretag; neutralitetsprincipen